2021
DOI: 10.3390/medicina57070699
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Multifidus Muscle Morphology Changes in Patient with Different Degrees of Lumbar Disc Herniation: An Ultrasonographic Study

Abstract: Background and Objective: Previous studies demonstrated that the prevalence of lumbar disc herniation (LDH) is relatively high. This investigation aimed to evaluate the size of lumbar multifidus (LM) muscle in patients with different degrees of LDH compared to healthy group, during rest and contraction, using ultrasonography. Materials and Methods: In this non-experimental, analytic, and case control study, ultrasound imaging was used to assess cross-sectional area (CSA) and thickness of the LM muscle in 15 he… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…[13] Furthermore, studies in LBP patients have revealed a decline in function and atrophy of the important trunk and low back deep musculature responsible for stability and coordination in particular the Multifidus muscle, a critical intersegmental lumbar spinal stabilizer. [14][15][16] In alignment with this research, the 8-week NeuroHAB ® program places a priority on retraining and reversing dysfunctional spinal, pelvic, and hip movement (Movement Dysfunction) by enhancing skill and stability compromised of the inter-related elements of coordinated-movement proficiency of the active musculature supported by the passive periarticular soft tissues. [17] CONCLUSION e results from this study support the alternative hypothesis, concluding an 8-week intervention of functional movement therapy represented by NeuroHAB ® results in a significant reduction of LBP ODI scores.…”
Section: Discussionmentioning
confidence: 88%
“…[13] Furthermore, studies in LBP patients have revealed a decline in function and atrophy of the important trunk and low back deep musculature responsible for stability and coordination in particular the Multifidus muscle, a critical intersegmental lumbar spinal stabilizer. [14][15][16] In alignment with this research, the 8-week NeuroHAB ® program places a priority on retraining and reversing dysfunctional spinal, pelvic, and hip movement (Movement Dysfunction) by enhancing skill and stability compromised of the inter-related elements of coordinated-movement proficiency of the active musculature supported by the passive periarticular soft tissues. [17] CONCLUSION e results from this study support the alternative hypothesis, concluding an 8-week intervention of functional movement therapy represented by NeuroHAB ® results in a significant reduction of LBP ODI scores.…”
Section: Discussionmentioning
confidence: 88%
“…Also, degenerative changes in the muscle affect functionality by causing a decrease in muscle thickness (12). It is stated that the lumbar multifidus muscle thickness is less in patients with low back pain (21,29). However, the difference that this situation creates between genders is not explained in the LSS.…”
Section: Discussionmentioning
confidence: 99%
“…This study determined that females with LSS had less multifidus muscle thickness at the L4/5 level. The change in muscle thickness also leads to a decrease in the muscle's ability to contract (29). This is important in maintaining balance and stability for the multifidus, a deep muscle of the lumbar region (13).…”
Section: Discussionmentioning
confidence: 99%
“…The percentage of MF atrophy correlated with the grade of disc degeneration [ 136 , 137 ]. In a case-control study, there was a significant correlation documented between functional disability, LBP intensity, and muscle size in LDH patients [ 138 ]. Choi et al.…”
Section: Paraspinal Muscles and Thoracic/lumbar Disordersmentioning
confidence: 99%